Aggregation of microplastic and biogenic particles in upper-ocean turbulence. (December 2022) - Rahmani, Mona; Gupta, Akanksha; Jofre, Lluís
Abstract: The aggregation of microplastic and biogenic particles in upper-ocean turbulence is studied by means of direct numerical simulations and Lagrangian tracking of point particles. The range of particle properties (size and density) and mixture characteristics (turbulence intensity and particle number densities) analyzed correspond to scenarios reminiscent of the problematic of microplastics in marine systems. A density ratio of 1.5 between the biogenic and microplastic particles, and varying diameter size and number density ratios are assumed. In particular, the focus is placed on the flow and mixture conditions encountered in the surface boundary layer (top region) of oceans, in which microplastics and biogenic particles have been experimentally observed to interact under significantly complex behaviors. The analysis consists of three principal parts involving the spatio-temporal distribution of the disperse and continuous phases, the mechanisms and rates of particle collisions, and the composition of the resulting aggregates. The main findings, for the range of parameters considered in this work and under the simplifying assumptions made in the model, are that (i) microplastics can be found in a large fraction of aggregates in scenarios with different average diameter of the mixture and number density ratios between microplastic and biogenic particles, (ii) microplastic-containing aggregates will sink to the deeper ocean layers particularly in situations where the biogenic particles are larger and/or of similar size than microplastics, and (iii) the Stokes numbers of aggregates tend not to be significantly different from the Stokes numbers of the initial individual microplastic and biogenic particles. In addition, by examining the collision mechanisms, a model for the collision rate that reproduces the computational results is proposed. Highlights: The aggregation of microplastics with biogenic particles can be an important mechanism for settling of microplastics. Microplastics were present in a significant number of aggregates in different scenarios. The percentage of total microplastics settling increased almost quadratically with the average diameter of the mixture.